Social Competence in Arabic Language Teaching: Insights from Faculty Members in Southeast Sulawesi - Muna, Wa (Institut Agama Islam Negeri Curup, 2024)
This study aims to analyse the social competence of lecturers in Arabic language learning at an Islamic College in Southeast Sulawesi using Adams GR's theory. Employing a descriptive qualitative method with a case study approach, data were collected through participant observation, interviews, and documentation. The research sample consists of six Arabic language lecturers teaching across four faculties at IAIN Kendari. Data analysis was conducted using reduction, presentation, and conclusion drawing techniques. The findings indicate that the lecturers exhibit strong social competence, evidenced by polite verbal communication, the use of sign language, written communication through technology, fairness towards students, and the provision of praise to enhance learning motivation. Based on these findings, it is concluded that empathy and fairness are key elements in fostering a positive learning atmosphere. These qualities contribute to a more inclusive, supportive environment that can enhance students’ emotional well-being and academic success. The study's implications suggest that integrating empathy and fairness in teaching practices is essential for promoting a conducive learning experience, thereby potentially improving student outcomes in higher education settings.